2008
DOI: 10.1111/j.1469-8986.2008.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized frontal activity elicited by attention‐directing visual and auditory cues

Abstract: In event-related potential studies of voluntary spatial attention, lateralized activity observed over anterior scalp sites prior to an impending target has been interpreted as the activity of a supramodal attentional control mechanism in the frontal lobes. However, variability in the scalp topography and presence of this activity across studies suggests that multiple neural generators contribute to the lateralized activity recorded at the scalp. Using distributed source modeling we found two distinct frontal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
8
36
0
Order By: Relevance
“…rather suggests that the ADAN reflects processes that are, at least in part, modality specific (Green et al, 2005;Green and McDonald, 2006; but see also Seiss et al, 2007). Correspondingly, Green et al (2008) have recently suggested that the ADAN reflects multiple neural generators that U N C O R R E C T E D P R O O F are differentially modulated by task parameters, such as cue modality and response related processes.…”
Section: Discussionmentioning
confidence: 99%
“…rather suggests that the ADAN reflects processes that are, at least in part, modality specific (Green et al, 2005;Green and McDonald, 2006; but see also Seiss et al, 2007). Correspondingly, Green et al (2008) have recently suggested that the ADAN reflects multiple neural generators that U N C O R R E C T E D P R O O F are differentially modulated by task parameters, such as cue modality and response related processes.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-automated procedure was used to discard epochs of EEG contaminated by blinks, eye movements, or excessive noise (Green et al, 2008). Any trial with an artifact within a 1 s interval (Ϫ200 to 800 ms poststimulus) was rejected.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the onset of the ADAN is delayed when it is more difficult to derive cue meaning (Jongen, Smulders, & Van Der Heiden, 2007). The amplitude of this component is also sensitive to other cue characteristics like the certainty with which it predicts target location (Seiss, Gherri, Eardley & Eimer, 2007;Green, Conder & McDonald, 2008). In addition, the amplitude of the ADAN is increased by spatial attention task demands when task irrelevant distractors are presented simultaneously with the target (Seiss, Driver & Eimer, 2009).…”
Section: Introductionmentioning
confidence: 99%